The Role Of Individual Characteristics And Labor Characteristics Toward Employee Productivity - Deni Widyo Prasetyo; Imam Ahya Uddin (JMD : Jurnal Riset Manajemen & Bisnis Dewantara, 2020)
This research was conducted to analyze the role of individual characteristics and job characteristics on productivity at PT. Sinar Niaga Sejahtera Mojagung. This type of research was explanatory research with a quantitative approach. The population in this study were 40 employees of PT. Sinar Niaga Sejahtera Mojagung and the samples used in the study were all population. The data used were primary in the form of a questionnaire. The analysis tool was a multiple linear regression with SPSS tools. The results showed that individual characteristics and company characteristics have a role in increasing employee productivity.